Thanatology Tourism in Nepal Himalayan Region: A Case of Langtang - Karki, Neeru (Journal of Tourism & Adventure, 2020)
On 25th April 2015 at 11:56 am local time, a devastating earthquake measuring 7.8 on the Richter scale shook Nepal. It is considered as one of the most fatal disasters in Nepal, ensuing aft restocks; avalanches and landslides triggered in the aftermath killed over 9,000 people. The most damage occurred when the earthquake triggered a destructive avalanche composed of ice, snow and soil, burying the entire Langtang village- a huge settlement of the popular adventure tourism destination of Nepal and killing at least 253 people. This study envisions to explore the scopes of special-interest dark (thanatology) tourism in the post-disaster scene, and it is used as a vehicle for self-reflection and education. This paper also explores the tourism prototype for an adventure tourism destination that has been severely impacted by a disaster. The paper adapts sociological theory, experience, and participant observation to complete a vanity ethnographic study of a “post-disaster tour” in the Langtang area. The tools and techniques of data collection derived from qualitative methodological approaches such as case study, semi-structured interviews, informal interviews, participant observation, content analysis, focus group discussions, in-depth interviews and house to house visit. The findings show how the adventure tourism hosts bounced back and depicted resiliency through unified reconstruction. Langtang’s post-disaster touristic setting instigates a unique paradigm in the tourism sector that can go parallel with the adventure tourism engagements. Th e model is represented through the amalgamation of dark tourism (Dark) and adventure tourism (Adventure), which forms a phenomenon that is named “darventure” (Kunwar, 2019) tourism. The‘ darventure’ tourism features the elements of both thanatology and frontier thrills at the same place. Dark tourist and adventure tourist experiences can coexist in Langtang, it creates a unique tourism prototype that complements both practices and can be offered as ‘darventure’ tourism.